One Year Follow up Study for Ozone and Fissure Sealant on Non-Cavitated Carious Lesions - Omar A. El Meligy; Abdullah S. Almushayt (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim of this study was to compare the effectiveness of ozone gas and fissure sealant in managing non-cavitated occlusal fissure carious lesions in first permanent molars. Fifty patients were selected from the Pediatric Dental Clinic, Faculty of Dentistry, King Abdulaziz University. Patients were divided into 2 groups; ozone group which included 50 teeth received ozone using the HealOzone device and sealant group which included 50 teeth received pits and fissure sealant. Patients were recalled for follow up after 3rd, 6th, 9th and 12th months for assessment of caries status and sealant retention. Non-cavitated stages; at 3 months and was found in ozone group, 23 cases were reversed and 26 cases were stable, and one case progressed. In sealant group; 47 cases were reversed and 2 cases were stable and one case progressed. At 12 months, in ozone group, 48 cases were reversed and 2 cases were stable and no case progressed, while in sealant group, 48 cases were reversed and 2 cases progressed. Ozone was as effective as the fissure sealant in managing active non-cavitated occlusal fissure carious lesions in first permanent molars.